The Effectiveness of Positive Reinforcement Techniques in Improving the Social Behavior of Blind Children - Putri Rulmayeni; Marlina Marlina (Edumaspul: Jurnal Pendidikan, 2024)
Visually impaired children generally have problems in social behavior, one of which is being very closed and quiet in the school environment. Based on the results of the assessment carried out, 2 visually impaired children were found in inclusive schools who had low social behavior. The purpose of this study is to test the effectiveness of positive reinforcement techniques in improving the social behavior of visually impaired children. The variables in this study are positive reinforcement techniques and social behavior of visually impaired children. This study uses a type of quantitative research through the Single Subject Research (SSR) approach. The research design used in this study is a multiple baseline cross subjects design. The research subjects were 2 visually impaired children in class XI at SMK Negeri 7 Padang. Data is collected through observation and tests. The data collection tool in this study is in the form of a social behavior assessment instrument. The data was analyzed using visual graphs consisting of in-condition analysis and inter-condition analysis. The results of the study showed an increase in social behavior in blind children in inclusion schools. This study uses positive reinforcement techniques in improving effective social behavior to be applied to blind children in inclusion schools.